Mustofa Azami’s Criticism of Joseph Schacht’s Thoughts on Hadits - Isnaeni, Ahmad; Mukri, Moh.; Muhsin, Masrukhin; Susanto, Is (KALAM, 2021)
Joseph Shacht a theory developer of the origin of hadits developed by Goldziher. The study of sanad has become a central topic that has received more attention. Some of the theories developed by Schacht lead to doubts about the authenticity of the hadits sanad. Sanad is only made by people who lived later and then leaned on to an authoritative figure to seek its legality. The results of this scientific work received criticism from Azami by bringing other evidence to rely on. The claim to the correctness of Schacht's theory is then considered not objective in terms of scientific truth standards. Some of the problems above are the focus of the study in this study, based on critical analysis methods and historical approaches. The result of the research is that the Sunnah is an expression, habit and way of life even though at that time the habits agreed by the community then relied on the Prophet. The more complete the series of sanads, as an indication, the further away from the Prophet's life. Sanad as a basis for dating a hadits. Even the appearance of sanad was earlier than the hadits editorial. Schacht based the development of the hadits sanad study through the theory of back projection and common link. Azami's criticism of Schacht's theory is as a baseless scientific lie. These theories stand on some of Schacht's misunderstanding of the theory and terms formulated by hadits scholars. Schacht's theory of the Sunnah also contradicts the historical realities prevailing in the early Islamic world.